The Impact of Microfinance on Rural Economic Growth: The Nigerian Experience - Nwude, E. Chuke; Anyalechi, Kenneth Chikezie (International Journal of Economics and Financial Issues, 2018)
The paper examines the impact of microfinance activities on rural economic growth and savings in Nigeria for the period 2000 – 2015. The ordinary least square regression was used as the technique of analysis. The findings show that the introduction of micro finance banking in Nigeria have not contributed to agricultural productivity but had assisted in increasing rural savings habits in Nigeria. As a means of improving rural economic growth in Nigeria the recommendations are that government should make conscious efforts to provide basic infrastructures in the rural areas to motivate micro finance institutions to locate their offices there; micro finance institutions should be encouraged to lend to rural dwellers based on relationship lending; some farm productive resources should be diversified to reduce farming risk, especially risk related to unpredictable extreme weather that may be due to climate change to increase productivity. Keywords: microfinance, economic growth, gross domestic product, rural savings, Nigeria. JEL Classifications: A10, A22, C32